"Living without knowing the past is to live in the dark": utopian and dystopian elements in the quest for the land without evil in A Tale of Love and Fury - ARAUJO, Kananda Monteiro (2023)
This paper aims to discuss the film A Tale of Love and Fury (2013), analyzing how some elements are connected in the narrative, such as, the cosmogony of the Land without Evil, the concept of collective memory and the dystopian genre are connected in the narrative. This comparative analysis of the work seeks to describe four moments in Brazilian history, the colonial Brazil, the Balaiada, the military dictatorship, and the emphasis in the last moment is directed to a future not far from today's "Rio de Janeiro 2096", this last moment is marked by the sub-element of dystopia and cyberpunk, that is, a dystopian future that is the result of the actions of the present and the past. Therefore, we seek to analyze these elements that make this work a reflection on the violence that perpetuates in society through the historical contextualization present in the narrative. Some important authors were essential to highlight these narrative moments, such as Helene Clastres (1978), José Varela (2002), Raquel Bittencourt (2008), Glaucio Aranha (2019), and Kaká Werá Jecupé (2020).